A survey on the performance of industrial and agricultural cooperative activities in a competitive market - Alireza Rabet; Moharram Ainollahi (تعاون و کشاورزی)
Context and purpose:This study was conducted to study the performance of agricultural and industrial cooperatives in Zanjan province in the competitive market space.Methodology/approach:In this study, 157 agricultural cooperatives and 93 industrial cooperatives out of a total of 265 agricultural and 123 industrial active cooperatives were selected and analyzed by stratified sampling method. To assess the appropriateness of the competitiveness indicators of cooperative enterprises, four indices including economic, social-cultural, managerial and infrastructural-institutional indicators were examined and evaluated.Findings and conclusions:The results of this study showed that among the surveyed indicators, economic and infrastructure indicators play a more important role in the competitiveness of cooperative enterprises with an average value of 3.37 and 3.36, respectively. In addition, in terms of socio-cultural and managerial indicators, the challenges for industrial cooperatives are more than agricultural cooperatives, while infrastructure and institutional challenges are more in agricultural cooperatives compared to industrial cooperatives. In planning and policy sub-indicators; knowledge and awareness, experience and expertise; industrial cooperatives have more problems than agricultural cooperatives. Forming cooperatives, marketing, commercializing, modifying the law to comprehensively support cooperatives, enhancing culture in the society, creating and enhancing social capital and improving investment security and private investment play an important role in the competitiveness of agricultural and industrial cooperatives.Originality/innovationPrevious studies have examined the status of agricultural or industrial cooperative enterprises, but this study simultaneously investigates and compares the situation of these enterprises in terms of competitiveness.